A Discourse on Literacy and Community: Research Relationships for Preservice Teachers - Karen Broaddus; David Landis (Networks: An Online Journal for Teacher Research, 1999)
This written dialogue between two university researchers explores how different forms of preservice teacher inquiry work as active components of language arts coursework in elementary education. We will discuss issues of design and implementation: 1. Theoretical contexts for including research in teacher education 2. Selecting settings for preservice teacher research 3. Defining research tasks 4. Examining professional research relationships 5. Forms for reflection 6. Analyzing research outcomes Our positions will be illustrated using the results of two distinct examples of literacy research: a study exploring the experiences of two preservice teachers conducting individual case studies of literacy development and a study examining a classroom-based research experience for one undergraduate.We will examine the role inquiry played in establishing professional relationships and how the three preservice teachers' use of language reflected their situational contexts– the social and cultural messages embedded in their stories of teaching and learning.